تقنيات الري الحديثة في محافظة النجف والإمكانات المكانية المتاحة - المظفر، صفاء مجيد عبدالصاحب Almuzaffar, Safa Majid Abdulsaheb (جامعة الكوفة - كلية الآداب, 2013)
The modern irrigation techniques are of great importance to irrigate crops and trees in arid and semi - arid and suffering from scarcity of water resources as the irrigation many ways, according to irrigated land and means many of the farmers saw their crops mainly by deliberate upon the nature of the crop is grown when they have the irrigation water equally hard, however many of them are using large amounts of irrigation may be due when it difficult to control in these waters so that the cost of maintaining the yield expected result to reduce wasteful consumption, and oftenirrigation is in excess of the need for costly or harmful entirely, is that bad selection or design of the proposed system for irrigation undoubtedly lead to low efficiency and poor utilization of water for irrigation, especially in the study area, which suffers from the problem of low levels of the Euphrates River. Knows irrigation as the water from reaching the soil and agricultural land, either by nature through precipitation types or industrial quantity required in a timely manner, this is linked to the process of irrigation Successful several objectives the most important of rationing water and soil conservation problem of salinization and was an old farmers using irrigation methods Traditional and after technological development became possible to use several methods lead to rationing of water and watering crops without excess, has been used in the study area are two of the ways of modern irrigation is drip irrigation and sprinkler irrigation, and is intended drip irrigation delivery of irrigation water to the plants the amount calculated in a manner slow points separate or continuously through small parts called emitters and is commonly used to irrigate crops, vegetables and shrubs ornamental and forestry projects and there are two types of irrigation in this way some of which are known to irrigation (surface) where the stretching lines emitters on the surface or buried emitters into the soil defines drip (under the surface) and are based on soil quality and the quality of the plant cultivated has been used this method of irrigation in the study area, especially in the Plateau area of Najaf, which are grown vegetable crops, as well as used to irrigate palm as also used in the irrigation of ornamental trees in the streets and squares in the city of Najaf, either spray irrigation is one of modern irrigation systems which are used to irrigate desert areas with sandy soil, which can not retain water for a long time that this kind of types of irrigation is suitable for most soils Najaf province, and uses this type of irrigation techniques for watering crops through the use of sprinklers in the form of rain industry has used spraying pivotal role in irrigate wheat and barley in Najaf Plateau has achieved great success has also been used to spray green squares in the city of Najaf. \ Through the study shows that the surface waters of the study area are suffering from the problem of low water levels and pollution problem as the use of traditional irrigation methods affect the water level on the one hand and increasing pollution of Education and decline in production on the other \ As it turns out through the study of groundwater in the study area are unfit for irrigation according Calibrator global irrigation as they affect the organizations irrigation and cause damage and Tsdi must therefore be filtered groundwater before delivery to organizations irrigation so as to keep them from damage and to improve production soil conservation and pollution, has been used as a water filtering system in the indicative farm typical of the Agriculture Department of Najaf, which has achieved outstanding production. \ As it turns out through the study that there is no right policies by the Ministry of Agriculture and Ministry of Water Resources to the Ministry of Environment to keep the water resources of the lower elevations and pollution and increase the production of agricultural land has fallen agricultural production in recent times so dramatically in the study area, in addition to the lack of the existence of a real and effective support to farmers in the study area, especially in Najaf and plateau of lack material support or Bttaghizhm of the modern irrigation techniques, Most farmers located at the plateau is undeveloped plastic tubes susceptible to damage as a result of saline groundwater.
Keywords: الري -- الموارد المائية العراقية -- محافظة النجف